2020
DOI: 10.1038/s41433-019-0762-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between ocular involvement and clinical manifestations, laboratory findings, and coronary artery dilatation in Kawasaki disease

Abstract: Objectives To assess the incidence of ocular manifestations of Kawasaki disease (KD) in children and to evaluate the relationship between ocular manifestations and the other clinical manifestations, laboratory findings, and echocardiographic findings. Methods Complete ophthalmologic examination and echocardiography were performed in 36 patients with KD during the acute phase before starting the treatment. Clinical manifestations and laboratory data including white blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…A 54-year-old female, with no significant past medical history, was The multisystem inflammatory syndrome that has developed the patient seems to be clinically similar to a Kawasaki-like disease which is known in pediatric population. Shiari et al 10 reported 36.1% of acute anterior uveitis in children with Kawasaki disease and found an association between uveitis and coronary artery dilatation. Another study found that the presence of anterior uveitis is helpful in the early diagnosis and treatment of incomplete Kawasaki disease and can be used as an additional diagnostic tool.…”
mentioning
confidence: 99%
“…A 54-year-old female, with no significant past medical history, was The multisystem inflammatory syndrome that has developed the patient seems to be clinically similar to a Kawasaki-like disease which is known in pediatric population. Shiari et al 10 reported 36.1% of acute anterior uveitis in children with Kawasaki disease and found an association between uveitis and coronary artery dilatation. Another study found that the presence of anterior uveitis is helpful in the early diagnosis and treatment of incomplete Kawasaki disease and can be used as an additional diagnostic tool.…”
mentioning
confidence: 99%
“…Platelets can act as the first responders in the recognition of pathogens. They rapidly generate host-defense peptides and then recruit and boost leukocytes to promote T cell-B cell crosstalk, which is necessary in adaptive immunity ( 41 43 ). In addition, platelets play an important role in injuring the vessel wall ( 4 , 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Shiari et al found that approximately 36.1% of children with Kawasaki disease present with anterior uveitis. 13 A study by Esteve-Sole et al, in 2021 implicated IFN-y in the pathogenesis of multi-system inflammatory syndrome in the setting of COVID-19. 14 Although no multi-system inflammatory syndrome was present in our patient's clinical course, our team hypothesizes that the inflammatory cascade initiated by SARS-CoV-2 infection likely triggered a first event anterior uveitis associated with HLA-B27.…”
Section: Discussionmentioning
confidence: 99%